Implementation of Gentle Parenting in the Era of Artificial Intelligence (AI): Penerapan Gentle Parenting dalam perkembangan Psikologis Anak di Era kecerdasan Buatan - Ama, Roy Gustaf Tupen; Widyayanti, Neni; Bete, Rufina Nenitriana S. (Psikologia : Jurnal Psikologi, 2025)
The development of the era and technology has led to the use of artificial intelligence (AI) in human activities. This is a challenge for parents in caring for and raising children so that they have good mental development when living side by side with artificial intelligence so that they do not experience problems such as mental health, low social and emotional skills, and critical thinking skills, so that the pattern of 'gentle parenting' appears to answer the challenges of parenting children in the era of artificial intelligence (AI). The method used in studying the topic above is qualitative with a literature review approach with the aim of examining the sources of articles published in journals whose article topics are in line with the theme of "gentle parenting. The page sources accessed in searching for articles consist of Sciencedirect, Emerlad, Scopus, Elsevier, Researchgate, Springer and Google Scholar. Based on the collection and review of articles conducted, it was found that the Implementation of the "Gentle Parenting" Parenting Pattern has a positive impact on children's mental health, children's emotional regulation, children's social skills in the learning process, children's emotional intelligence, discipline, and children's critical thinking skills and creativity in facing challenges in the Era of Artificial Intelligence (AI) Higlights: Gentle parenting enhances children's emotional intelligence and social skills in the AI era. It promotes better mental health and emotional regulation in children. The approach fosters critical thinking, creativity, and discipline in children. Keywords: Gentle Parenting, Artificial Intelegence, Child Development